ANALISIS PENGARUH MODAL USAHA DAN KREATIVITAS TERHADAP PENGEMBANGAN USAHA PENJAHIT PAKAIAN DI KABUPATEN MIMIKA - Siti Mahmudah; Rulan. L Manduapessy (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims to determine the influence of business capital and creativity on clothing sewing businesses in Mimika district. The research method used is the associative research method, namely the associative research method is research that looks for causal relationships or influences, namely the relationship or influence of the independent variable (Business Capital) on the dependent variable (Business Development). This research aims to determine the influence of business capital and creativity on the development of tailoring businesses in the city of Timika. In this research the methods used were observation, interviews, questionnaires. SEM-PLS analysis, namely Partial Least Square-Structural Equation Modeling (PLS-SEM) is a test carried out without a valid theoretical basis, ignoring several assumptions, and knowing the accuracy parameters of the estimated model which can be seen from the coefficient of determination (R2) by using the SmartPLS4 application. The research results stated that the T-statistic value for the variable was 3,571 > 1.96 and the P-Value was 0, less than 0.05. This shows that business capital has a positive and significant influence on the development of sewing service businesses in Mimika district. So the first assumption is "accepted". Meanwhile, for the creativity variable, the T-statistic value is 1.987 which is greater than the t-table sig 5% = 1.96 and the P-value is 0.047 which is smaller than 0.05. So the second assumption is "accepted